The libido, scrotal circumference, sperm quality, and testosterone levels of matured boer ducks supplemented with selenium - N. S., Mariani; M., Wan Zahari; A. M., Marini; A., Abd. Rahman; S., Shanmugavelu; H., Yaakub (Bogor Agricultural University, 2022)
A study was conducted to determine the effect of three levels of selenium (Se) supplementation on the libido, scrotal circumference, sperm quality, and testosterone levels in matured Boer bucks. The feeding trial was conducted at MARDI Bachok Station, Bachok, Kelantan, Malaysia, for over six months. A total of 18 matured Boer bucks aged two years with an initial body weight of 53.28±0.62 kg, and no experience of sexual activity was selected for the feeding trial. All animals were randomly divided into three dietary treatments based on a completely randomized design (CRD). Group A and B were supplemented with organic Se at doses of 0.18 mg/kg DM and 0.36 mg/kg DM, respectively, whereas group C acted as a control group (without Se supplementation). Their basal diet consisted of 60% formulated pellet and 40% Brachiaria dictyoneura grass. Daily feed offered (DM basis) was based on 3% of mean body weight. Libido, scrotal circumference, and sperm quality were measured every two months during the feeding trial. Testosterone levels were determined at the end of the feeding trial. The results indicated that the basal diet (control group) was deficient in Se, with the concentration of 0.004 mg/kg. Supplementation of 0.18 mg Se/kg DM only improved the libido and sperm quality (p<0.05). Supplementation of 0.36 mg Se/kg DM significantly (p<0.05) increased libido, sperm quality, and testosterone levels. It is summarized that supplementation of 0.36 mg Se/kg DM has the potential to improve the reproductive performance of bucks, although it occurred at the adult stage.